Blade Profile Optimization of Kaplan Turbine Using CFD Analysis - Aijaz Bashir Janjua; Muhammad Shahid Khalil; Muhammad Saeed (Mehran University Research Journal of Engineering and Technology, 2013)
Utilization of hydro-power as renewable energy source is of prime importance in the world now. Hydropower energy is available in abundant in form of falls, canals rivers, dams etc. It means, there are various types of sites with different parameters like flow rate, heads, etc. Depending upon the sites, water turbines are designed and manufactured to avail hydro-power energy. Low head turbines on runof-river are widely used for the purpose. Low head turbines are classified as reaction turbines. For runof river, depending upon the variety of site data, low head Kaplan turbines are selected, designed and manufactured. For any given site requirement, it becomes very essential to design the turbine runner blades through optimization of the CAD model of blades profile. This paper presents the optimization technique carried out on a complex geometry of blade profile through static and dynamic computational analysis. It is used through change of the blade profile geometry at five different angles in the 3D (Three Dimensional) CAD model. Blade complex geometry and design have been developed by using the coordinates point system on the blade in PRO-E /CREO software. Five different blade models are developed for analysis purpose. Based on the flow rate and heads, blade profiles are analyzed using ANSYS software to check and compare the output results for optimization of the blades for improved results which show that by changing blade profile angle and its geometry, different blade sizes and geometry can be optimized using the computational techniques with changes in CAD models.